Stain-resistant and mildew-proof single-component deacetic acid silicone rubber sealing material

By sodium modification and cross-linked dextran modification of precipitation method white carbon black, the problem of reducing tensile strength and durability of sealing materials in high chloride ion environments is solved, and higher mechanical properties and antibacterial and anti-mold properties are achieved.

CN119505800AInactive Publication Date: 2025-02-25SHANDONG JINGMAO NEW MATERIAL CO LTD
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202510089498.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-21
Publication Date
2025-02-25
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

When using precipitation white carbon black as a reinforcement filler, the existing single-component silicone acetate rubber sealing material is immersed in water for a long time, especially in a high chloride environment, resulting in a decrease in its tensile strength and tear-break elongation and shortening its service life.

Method used

By performing two-step modification of the precipitation method, sodium modification and cross-linked dextran modification, it improves its tensile bonding strength and durability in a high chloride ion environment, and uses it as a reinforcement filler for the sealing material.

Benefits of technology

The tensile bonding strength and durability of the sealing material are significantly improved, especially in high chloride ion environments, maintaining high mechanical properties and antibacterial and anti-mold properties.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
  • Figure SMS_3
    Figure SMS_3
Patent Text Reader

Abstract

The invention discloses a stain-resistant and mildew-proof single-component deacetic acid silicone rubber sealing material, and belongs to the field of adhesive materials. The sealing material is prepared from the following raw material components: alpha, omega-dihydroxy polydimethylsiloxane, simethicone, cross-linked glucan modified precipitated white carbon black, a cross-linking agent and an organic tin catalyst. The sealing material disclosed by the invention has relatively excellent chloride ion resistance, and after the sealing material is soaked in an environment with the chloride ion concentration of 200ppm for 168 hours, the tensile adhesive strength is 3.55-3.61 MPa; the elongation at the maximum tensile strength is 529-542%; the bonding damage area is 8.7 to 9.5 percent; after the coating is soaked in an environment with the chloride ion concentration of 19000 ppm for 168 hours, the tensile adhesive strength of the coating is 3.38-3.44 MPa; the elongation at the maximum tensile strength is 496-512%; and the bonding damage area is 9.4%-10.1%.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a single-component deacetated silicone rubber sealing material which is resistant to dirt and mildew, and belongs to the field of adhesive materials. Background Art

[0002] Single-component room temperature vulcanized silicone rubber is a type of silicone product that is mixed and packaged in a sealed container (hose or seal), squeezed out of the sealed container when in use, and cross-linked into an elastomer after contact with moisture in the air. According to the structure of the vulcanization by-products, it can be divided into six types: acetic acid type, ketoxime type, alcohol type, amine type, amide type and acetone type. The first three are currently the most widely used.

[0003] Deacetic acid-free one-component RTV silicone rubber has a pungent odor and is somewhat corrosive to metals, but has very good adhesion to materials such as glass. It is mainly used as a building sealant to seal the joints of glass, ceramic tiles, aluminum frames, etc. One of the typical applications of deacetic acid-free one-component RTV silicone rubber is the bonding and sealing of large glass panels, fish tanks, aquariums, etc., which requires very high adhesion between the sealant and the substrate, especially after immersion in water.

[0004] Silicone rubber is a non-crystalline polymer with weak interaction between molecular chains. Unreinforced vulcanized rubber has very poor strength and is worthless. The common method is to add a certain amount of filler to improve performance. Fillers are divided into reinforcing fillers, such as silicon dioxide; semi-reinforcing fillers, such as light calcium carbonate; and incremental fillers, such as quartz powder, diatomaceous earth, and heavy calcium carbonate. White carbon black has a small particle size, a large specific surface area, and a high surface activity. In addition, the structure of white carbon black is similar to the molecular structure of silicone rubber, so it is an ideal reinforcing filler for sealing materials.

[0005] The purity of fumed silica is relatively high, usually above 99%. Fewer impurities make the sealing material have better performance, especially shorter surface vulcanization time and higher shear strength after vulcanization. However, since the surface hydroxyl group of fumed silica is less than that of precipitated silica, when fumed silica is used as a reinforcing filler, the tensile bond strength of the sealing material after curing is lower than that of the sealing material using precipitated silica. In addition, the price of fumed silica is generally higher, 5-8 times that of precipitated silica, which invisibly increases the cost of the sealing material.

[0006] The purity of precipitated silica is about 95%, which can bring price advantages and improve the bonding strength of sealing materials. However, it also contains high impurities and poor water adhesion. In the bonding and sealing scenarios of fish tanks, aquariums, etc., due to contact with water, long-term immersion will cause its tensile strength and elongation to decrease, especially when there are chloride ions in the water. As the concentration of chloride ions increases, the degree of reduction in tensile strength and elongation at break is particularly serious. The water quality in glass containers such as fish tanks and aquariums changes frequently, which further aggravates this situation.

[0007] In summary, the one-component deacetated silicone rubber sealing material in the prior art can effectively reduce costs and increase the tensile bonding strength after curing when using precipitated silica as a reinforcing filler. However, when it is used as a sealing material for fish tanks, aquariums, etc., after long-term contact and immersion in water, its tensile strength and elongation at break will decrease, especially when the water contains chloride ions. As the chloride ion concentration increases, the degree of reduction in tensile strength and elongation at break becomes more serious. Summary of the invention

[0008] The technical problem to be solved by the present invention is to overcome the defects of the prior art by subjecting the lower-cost precipitated silica to two-step modification, including sodium modification and cross-linked dextran modification, and then using it as a reinforcing filler for sealing materials. This increases the tensile bonding strength of the sealing materials while maintaining relatively excellent tensile properties in a high chloride ion environment.

[0009] In order to solve the above technical problems, the present invention adopts the following technical solutions: A single-component deacetated silicone rubber sealing material that is resistant to dirt and mildew. The raw material components of the sealing material consist of α, ω-dihydroxy polydimethylsiloxane, dimethyl silicone oil, cross-linked dextran-modified precipitated silica, a cross-linking agent, and an organic tin catalyst. The mass ratio of the components is 110-140:30-40:14-16:6-8:4.5-5.5.

[0010] The following are further improvements to the above technical solution: The cross-linking agent is methyltriacetoxysilane; The organotin catalyst is dibutyltin diacetate; The preparation method of the cross-linked dextran-modified precipitated silica comprises sodium modification of the precipitated silica and cross-linked dextran modification; The method for modifying sodium precipitated silica is as follows: The method for sodium modification of precipitated silica comprises washing the precipitated silica with deionized water at 45-55° C. until the conductivity of the deionized water is less than 1.5-2.0 μs / cm, stopping washing, and then drying to constant weight to obtain washed precipitated silica, and then mixing the washed precipitated silica, sodium hydroxide, aluminum hydroxide, sodium silicate, and solvent deionized water, controlling the temperature to 66-70° C., stirring for 280-320 min, and filtering, washing, and drying after stirring to obtain sodium-modified precipitated silica; The mass ratio of the precipitated white carbon black, sodium hydroxide, aluminum hydroxide, sodium silicate, and deionized water for solvent is 85-115:3.5-4.5:11-13:17-23:110-140; The purity of the precipitated silica is 95.44 wt%, the particle size is 15 μm, and the specific surface area is 177 m 2 / g.

[0011] The method for modifying the cross-linked dextran is: The cross-linked dextran is mixed with an acetic acid solution, stirred to completely dissolve, and a cross-linked dextran solution is obtained. The cross-linked dextran solution is then heated to 92-97° C., polyvinyl alcohol is added, and stirring is continued for 15-25 minutes. Then, sodium-modified precipitated silica and N,N-methylenebisacrylamide are added, the temperature is kept constant, and stirring is continued for 65-75 minutes. After the stirring is completed, filtering, washing, and drying are performed, and then the temperature is controlled to 405-420° C. The dried product is subjected to high-temperature treatment for 110-130 minutes. After the treatment is completed, cooling is performed to obtain cross-linked dextran-modified precipitated silica; The mass ratio of the cross-linked dextran to the acetic acid solution is 1:6.5-7.5; The model of the cross-linked dextran is G15; The concentration of the acetic acid solution is 4.5-5.5wt%; The mass ratio of the cross-linked dextran solution, polyvinyl alcohol, sodium-modified precipitated silica, and N,N-methylenebisacrylamide is 700-800:75-125:250-350:0.9-1.1.

[0012] The preparation method of the sealing material is as follows: The mixer is adjusted to a vacuum state, α, ω-dihydroxy polydimethylsiloxane is added into the mixer and stirred for 15-25 minutes, then a cross-linking agent is added and the stirring is continued for 10-20 minutes, then cross-linked dextran-modified precipitated silica and dimethyl silicone oil are added and the stirring is continued for 15-25 minutes, and finally an organic tin catalyst is added and stirred for 25-35 minutes, and then the material is discharged and packaged to obtain a single-component deacetated silicone rubber sealing material that is resistant to stains and mildew.

[0013] Compared with the prior art, the present invention achieves the following beneficial effects: The sealing material of the present invention has relatively excellent mechanical properties. According to the method in GB / T29755-2013, mechanical property tests are carried out, including tensile bonding strength, maximum tensile strength time ratio, Shore hardness, elastic recovery rate, and bonding failure area. The tensile bonding strength is 3.58-3.66MPa; the elongation at maximum tensile strength is 543-552%; the Shore hardness is 34-35, the elastic recovery rate is 91.8-92.4%; the bonding failure area is 8.2-8.6%; The sealing material of the present invention has relatively excellent performance in use. According to the method in HG / T5378-2018, the performance test is carried out, including surface drying time, extrusion property, and curing depth. The surface drying time is 14-15min; the extrusion property is 4-5s / 20g; and the curing depth is 5.2-5.5mm / 24h; The sealing material of the present invention has relatively excellent aging resistance. According to the method in GB / T29755-2013, hot air aging is carried out, and the tensile bonding strength, maximum tensile strength time rate, and bonding failure area after hot air aging are tested. The tensile bonding strength is 3.47-3.62MPa; the elongation at the maximum tensile strength is 525-537%; the bonding failure area is 9.1-9.4%; The sealing material of the present invention has relatively excellent chloride ion resistance. According to the method in GB / T29755-2013, a sample is prepared, and then the sample is completely immersed in water with different chloride ion concentrations, the chloride ion concentrations are 200ppm and 19000ppm, respectively, and the immersion time is 168h. After the immersion is completed, according to the method in GB / T29755-2013, the tensile bond strength, the maximum tensile strength time rate, and the bonding failure area are detected. When the chloride ion concentration is 200ppm, the tensile bond strength is 3.55-3.61MPa; the elongation at the maximum tensile strength is 529-542%; and the bonding failure area is 8.7-9.5%; when the chloride ion concentration is 19000ppm, the tensile bond strength is 3.38-3.44MPa; the elongation at the maximum tensile strength is 496-512%; and the bonding failure area is 9.4-10.1%; The sealing material of the present invention has low thermal weight loss. According to the method in GB / T29755-2013, the thermal weight loss is 1.9-2.3%; The sealing material of the present invention has a low water vapor permeability. According to the method in GB / T29755-2013, the water vapor permeability is tested and the water vapor permeability is 1.15-1.21 g / (m 2 ·d); The sealing material of the present invention has good antibacterial and mildew proof properties. According to the method in GB / T13477.25-2024, the antibacterial and mildew proof properties are tested. The test strains include Penicillium sphenanthellum, Penicillium citrinum, Trichoderma viride, and Sphaerotheca brevis. The mildew resistance level is used as an evaluation index, and the mildew resistance levels of these four mildews are all level 0. DETAILED DESCRIPTION Example 1

[0014] A stain-resistant and mildew-proof one-component deacetated silicone rubber sealing material, wherein the raw material components are composed of α, ω-dihydroxy polydimethylsiloxane, dimethyl silicone oil, cross-linked dextran-modified precipitated silica, a cross-linking agent, and an organic tin catalyst, and the mass ratio of the components is 125:35:15:7:5; The cross-linking agent is methyltriacetoxysilane; The organotin catalyst is dibutyltin diacetate; The preparation method of the cross-linked dextran-modified precipitated silica comprises sodium modification of the precipitated silica and cross-linked dextran modification; The method for modifying the precipitated white carbon black sodium is as follows: The precipitated silica is washed with 50° C. deionized water until the conductivity of the deionized water is less than 1.8 μs / cm, the washing is stopped, and then the washed precipitated silica is dried to constant weight to obtain the washed precipitated silica, and then the washed precipitated silica, sodium hydroxide, aluminum hydroxide, sodium silicate, and solvent are mixed with deionized water, the temperature is controlled to be 68° C., and the stirring is performed for 300 minutes. After the stirring is completed, the mixture is filtered, washed, and dried to obtain sodium-modified precipitated silica; The mass ratio of the precipitated white carbon black, sodium hydroxide, aluminum hydroxide, sodium silicate, and deionized water for solvent is 100:4:12:20:125; The purity of the precipitated silica is 95.44 wt%, the particle size is 15 μm, and the specific surface area is 177 m 2 / g.

[0015] The method for modifying the cross-linked dextran is: The cross-linked dextran is mixed with the acetic acid solution, stirred to completely dissolve, and a cross-linked dextran solution is obtained. The cross-linked dextran solution is then heated to 95°C, polyvinyl alcohol is added, and stirring is continued for 20 minutes. Then, sodium-modified precipitated silica and N,N-methylenebisacrylamide are added, the temperature is kept constant, and stirring is continued for 70 minutes. After the stirring is completed, filtering, washing, and drying are performed, and then the temperature is controlled to 415°C, and the dried product is subjected to high-temperature treatment for 120 minutes. After the treatment is completed, cooling is performed to obtain cross-linked dextran-modified precipitated silica; The mass ratio of the cross-linked dextran to the acetic acid solution is 1:7; The model of the cross-linked dextran is G15; The concentration of the acetic acid solution is 5wt%; The mass ratio of the cross-linked dextran solution, polyvinyl alcohol, sodium-modified precipitated silica, and N,N-methylenebisacrylamide is 750:100:300:1.

[0016] The preparation method of the sealing material is as follows: The mixer was adjusted to a vacuum state, α, ω-dihydroxypolydimethylsiloxane was added into the mixer and stirred for 20 minutes, then a cross-linking agent was added and stirring was continued for 15 minutes, then cross-linked dextran-modified precipitated silica and dimethyl silicone oil were added and stirring was continued for 20 minutes, finally an organic tin catalyst was added and stirred for 30 minutes, and then the mixture was discharged and packaged to obtain a single-component deacetated silicone rubber sealing material that is resistant to stains and mildew. Example 2

[0017] A single-component deacetated silicone rubber sealing material that is resistant to stains and mildew, wherein the raw material components are composed of α, ω-dihydroxy polydimethylsiloxane, dimethyl silicone oil, cross-linked dextran-modified precipitated silica, a cross-linking agent, and an organic tin catalyst, and the mass ratio of the components is 110:30:14:6:4.5; The cross-linking agent is methyltriacetoxysilane; The organotin catalyst is dibutyltin diacetate; The preparation method of the cross-linked dextran-modified precipitated silica comprises sodium modification of the precipitated silica and cross-linked dextran modification; The method for modifying the precipitated white carbon black sodium is as follows: The precipitated silica is washed with 45° C. deionized water until the conductivity of the deionized water is less than 1.5 μs / cm, the washing is stopped, and then the washed precipitated silica is dried to constant weight to obtain the washed precipitated silica, and then the washed precipitated silica, sodium hydroxide, aluminum hydroxide, sodium silicate, and solvent are mixed with deionized water, the temperature is controlled to be 66° C., and the stirring is performed for 320 min. After the stirring is completed, the mixture is filtered, washed, and dried to obtain sodium-modified precipitated silica; The mass ratio of the precipitated white carbon black, sodium hydroxide, aluminum hydroxide, sodium silicate, and deionized water for solvent is 85:3.5:11:17:110; The purity of the precipitated silica is 95.44 wt%, the particle size is 15 μm, and the specific surface area is 177 m 2 / g.

[0018] The method for modifying the cross-linked dextran is: The cross-linked dextran is mixed with the acetic acid solution, stirred to completely dissolve, and a cross-linked dextran solution is obtained. The cross-linked dextran solution is then heated to 92°C, polyvinyl alcohol is added, and stirring is continued for 25 minutes. Then, sodium-modified precipitated silica and N,N-methylenebisacrylamide are added, the temperature is kept constant, and stirring is continued for 65 minutes. After the stirring is completed, filtering, washing, and drying are performed, and then the temperature is controlled to 405°C, and the dried product is subjected to high-temperature treatment for 130 minutes. After the treatment is completed, cooling is performed to obtain cross-linked dextran-modified precipitated silica; The mass ratio of the cross-linked dextran to the acetic acid solution is 1:6.5; The model of the cross-linked dextran is G15; The concentration of the acetic acid solution is 4.5wt%; The mass ratio of the cross-linked dextran solution, polyvinyl alcohol, sodium-modified precipitated silica, and N,N-methylenebisacrylamide is 700:75:250:0.9.

[0019] The preparation method of the sealing material is as follows: The mixer was adjusted to a vacuum state, α, ω-dihydroxypolydimethylsiloxane was added into the mixer and stirred for 15 minutes, then a cross-linking agent was added and stirring was continued for 20 minutes, then cross-linked dextran-modified precipitated silica and dimethyl silicone oil were added and stirring was continued for 15 minutes, finally an organic tin catalyst was added and stirring was continued for 35 minutes, and then the material was discharged and packaged to obtain a single-component deacetated silicone rubber sealing material that is resistant to stains and mildew. Example 3

[0020] A stain-resistant and mildew-proof one-component deacetated silicone rubber sealing material, wherein the raw material components are composed of α, ω-dihydroxy polydimethylsiloxane, dimethyl silicone oil, cross-linked dextran-modified precipitated silica, a cross-linking agent, and an organic tin catalyst, and the mass ratio of the components is 140:40:16:8:5.5; The cross-linking agent is methyltriacetoxysilane; The organotin catalyst is dibutyltin diacetate; The preparation method of the cross-linked dextran-modified precipitated silica comprises sodium modification of the precipitated silica and cross-linked dextran modification; The method for modifying the precipitated white carbon black sodium is as follows: The precipitated silica is washed with 55° C. deionized water until the conductivity of the deionized water is less than 2.0 μs / cm, the washing is stopped, and then the washed precipitated silica is dried to constant weight to obtain the washed precipitated silica, and then the washed precipitated silica, sodium hydroxide, aluminum hydroxide, sodium silicate, and solvent are mixed with deionized water, the temperature is controlled to 70° C., and the stirring is performed for 280 min. After the stirring is completed, the mixture is filtered, washed, and dried to obtain sodium-modified precipitated silica; The mass ratio of the precipitated white carbon black, sodium hydroxide, aluminum hydroxide, sodium silicate, and deionized water for solvent is 115:4.5:13:23:140; The purity of the precipitated silica is 95.44 wt%, the particle size is 15 μm, and the specific surface area is 177 m 2 / g.

[0021] The method for modifying the cross-linked dextran is: The cross-linked dextran is mixed with the acetic acid solution, stirred to completely dissolve, and a cross-linked dextran solution is obtained. The cross-linked dextran solution is then heated to 97°C, polyvinyl alcohol is added, and stirring is continued for 15 minutes. Then, sodium-modified precipitated silica and N,N-methylenebisacrylamide are added, the temperature is kept constant, and stirring is continued for 75 minutes. After the stirring is completed, filtering, washing, and drying are performed, and then the temperature is controlled to 420°C, and the dried product is subjected to high-temperature treatment for 110 minutes. After the treatment is completed, cooling is performed to obtain cross-linked dextran-modified precipitated silica. The mass ratio of the cross-linked dextran to the acetic acid solution is 1:7.5; The model of the cross-linked dextran is G15; The concentration of the acetic acid solution is 5.5wt%; The mass ratio of the cross-linked dextran solution, polyvinyl alcohol, sodium-modified precipitated silica, and N,N-methylenebisacrylamide is 800:125:350:1.1.

[0022] The preparation method of the sealing material is as follows: The mixer was adjusted to a vacuum state, α, ω-dihydroxypolydimethylsiloxane was added into the mixer and stirred for 25 minutes, then a cross-linking agent was added and stirring was continued for 10 minutes, then cross-linked dextran-modified precipitated silica and dimethyl silicone oil were added and stirring was continued for 25 minutes, finally an organic tin catalyst was added and stirred for 25 minutes, and then the mixture was discharged and packaged to obtain a single-component deacetated silicone rubber sealing material that is resistant to stains and mildew.

[0023] Comparative Example 1 Different from Example 1, in the preparation method of cross-linked dextran-modified precipitated silica, the step of sodium modification of precipitated silica is omitted, and the untreated precipitated silica is directly modified with cross-linked dextran, and is used as a raw material for the sealing material while keeping the dosage unchanged; The remaining steps remain unchanged and the sealing material is prepared.

[0024] Comparative Example 2 Different from Example 1, the cross-linked dextran modification step in the preparation method of the cross-linked dextran-modified precipitated silica is omitted, and the sodium-modified precipitated silica obtained in the sodium modification step of the precipitated silica is directly used as the raw material of the sealing material while keeping the dosage unchanged; The remaining steps remain unchanged and the sealing material is prepared.

[0025] Test Example 1 Mechanical Properties Test The sealing materials of Examples 1-3 and Comparative Examples 1-2 were subjected to mechanical property tests according to the method in GB / T29755-2013, including tensile bond strength, maximum tensile strength time ratio, Shore hardness, elastic recovery rate, and bonding failure area. The results are shown in Table 1.

[0026] Table 1

[0027] In Example 1-3, precipitated silica is modified in two steps, including sodium modification and cross-linked dextran modification, and then used as a reinforcing filler for a sealing material. The final sealing material has excellent mechanical properties, high tensile bond strength, maximum tensile strength time ratio, Shore hardness, elastic recovery rate, and small bonding failure area. Comparative Example 1 In the preparation method of precipitated silica modified with cross-linked dextran, the sodium modification step of precipitated silica is omitted, and the untreated precipitated silica is directly modified with cross-linked dextran. When the amount remains unchanged, it is used as a raw material for sealing materials, which will lead to a decrease in the mechanical properties of the sealing materials, among which the decrease in hardness is the most obvious. In addition, the tensile bond strength, the maximum tensile strength time rate, and the elastic recovery rate all decrease to a certain extent, and the bonding failure area increases to a certain extent; In the preparation method of precipitated silica modified with cross-linked dextran, the cross-linked dextran modification step is omitted, and the sodium-modified precipitated silica obtained in the sodium modification step of the precipitated silica is directly used as the raw material of the sealing material while keeping the dosage unchanged. This will lead to a decrease in the mechanical properties of the sealing material, with the tensile bonding strength, maximum tensile strength time rate, and elastic recovery rate decreasing particularly significantly. In addition, the hardness also decreases to a certain extent, and the bonding failure area increases significantly.

[0028] Test Example 2: Performance Test The sealing materials of Examples 1-3 and Comparative Examples 1-2 were subjected to performance tests according to the method in HG / T5378-2018, including surface drying time, extrudability, and curing depth. The results are shown in Table 2.

[0029] Table 2

[0030] In Example 1-3, precipitated silica is modified in two steps, including sodium modification and cross-linked dextran modification, and then used as a reinforcing filler for a sealing material. The sealing material has excellent performance, short surface drying time, good extrudability, and high curing depth. Comparative Example 1 In the preparation method of cross-linked dextran-modified precipitated silica, the sodium modification step of precipitated silica is omitted, and the untreated precipitated silica is directly modified with cross-linked dextran. When the amount remains unchanged, it is used as a raw material for sealing materials, which will lead to a decrease in the performance of the sealing materials, among which the extrusion performance decreases most significantly, the extrusion time increases significantly, and the surface drying time is also longer, and the curing depth is lower; In Comparative Example 2, in the preparation method of precipitated silica modified with cross-linked dextran, the cross-linked dextran modification step is omitted, and the sodium-modified precipitated silica obtained in the sodium modification step of the precipitated silica is directly used as a raw material for sealing materials while keeping the dosage unchanged. This will lead to a decrease in the performance of the sealing materials, wherein the surface drying time is significantly increased, the curing depth is significantly reduced, the extrusion time is increased to a certain extent, and the extrusion property is slightly reduced.

[0031] Test Example 3 Aging resistance test The sealing materials of Examples 1-3 and Comparative Examples 1-2 were subjected to hot air aging according to the method in GB / T29755-2013, and the tensile bond strength, maximum tensile strength time rate, and bonding failure area after hot air aging were tested. The results are shown in Table 3.

[0032] Table 3

[0033] In Example 1-3, precipitated silica is modified in two steps, including sodium modification and cross-linked dextran modification, and then used as a reinforcing filler for a sealing material. The sealing material has excellent aging resistance and can still maintain a high tensile bond strength, maximum tensile strength time rate, and a low bond failure area after aging. Comparative Example 1 In the preparation method of cross-linked dextran-modified precipitated silica, the sodium modification step of precipitated silica is omitted, and the untreated precipitated silica is directly modified with cross-linked dextran. When the amount remains unchanged, it is used as a raw material for sealing materials, which will lead to a decrease in the aging resistance of the sealing material, a certain degree of decrease in the tensile bonding strength and the maximum tensile strength time rate, and a certain degree of increase in the bonding failure area; In the preparation method of precipitated silica modified with cross-linked dextran in Comparative Example 2, the cross-linked dextran modification step is omitted, and the sodium-modified precipitated silica obtained in the sodium modification step of the precipitated silica is directly used as the raw material of the sealing material while keeping the dosage unchanged. This will lead to a decrease in the aging resistance of the sealing material, a serious decrease in the tensile bonding strength and the maximum tensile strength time rate, and a serious increase in the bonding failure area.

[0034] Test Example 4 Chloride ion resistance test The sealing materials of Examples 1-3 and Comparative Examples 1-2 were prepared into samples according to the method in GB / T29755-2013, and then the samples were completely immersed in water with different concentrations of chloride ions, the concentrations of chloride ions were 200 ppm and 19000 ppm, respectively, and the immersion time was 168 h. After the immersion was completed, the tensile bond strength, maximum tensile strength time rate, and bond failure area were tested according to the method in GB / T29755-2013. The results are shown in Table 4.

[0035] Table 4

[0036] In Example 1-3, precipitated silica is modified in two steps, including sodium modification and cross-linked dextran modification, and then used as a reinforcing filler for a sealing material. The sealing material has excellent chloride ion resistance and can still maintain a high tensile bond strength, maximum tensile strength time ratio, and a low bond failure area after being immersed in chloride ion environments of different concentrations. Comparative Example 1 In the preparation method of precipitated silica modified with cross-linked dextran, the sodium modification step of precipitated silica is omitted, and the untreated precipitated silica is directly modified with cross-linked dextran. When the amount remains unchanged, it is used as a raw material for a sealing material, which will cause the chloride ion resistance of the sealing material to decrease. With the increase of chloride ion concentration, the tensile bond strength and the maximum tensile strength time rate of the material are greatly reduced, and the bonding failure area is greatly increased; In the preparation method of precipitated silica modified with cross-linked dextran, the cross-linked dextran modification step is omitted, and the sodium-modified precipitated silica obtained in the sodium modification step of the precipitated silica is directly used as the raw material of the sealing material while keeping the dosage unchanged. This will cause the chloride ion resistance of the sealing material to decrease. With the increase of chloride ion concentration, the tensile bonding strength and the maximum tensile strength time rate of the material will seriously decrease, and the bonding failure area will seriously increase.

[0037] Test Example 5 Thermal Weight Loss Performance Test The sealing materials of Examples 1-3 and Comparative Examples 1-2 were subjected to a thermal gravimetric test according to the method in GB / T29755-2013. The results are shown in Table 5.

[0038] Table 5

[0039] In Example 1-3, precipitated silica is modified in two steps, including sodium modification and cross-linked dextran modification, and then used as a reinforcing filler for a sealing material. The sealing material has excellent heat loss resistance and a low heat loss percentage. Comparative Example 1 In the preparation method of cross-linked dextran-modified precipitated silica, the sodium modification step of precipitated silica is omitted, and the untreated precipitated silica is directly modified with cross-linked dextran. When the amount remains unchanged, it is used as a raw material for the sealing material, which will cause the heat weight loss resistance of the sealing material to decrease and the percentage of heat weight loss to increase seriously; In the preparation method of precipitated silica modified with cross-linked dextran in Comparative Example 2, the cross-linked dextran modification step is omitted, and the sodium-modified precipitated silica obtained in the sodium modification step of the precipitated silica is directly used as the raw material of the sealing material while keeping the dosage unchanged. This will cause the heat-resistant weight loss performance of the sealing material to decrease and the percentage of heat weight loss to increase to a large extent.

[0040] Test Example 6 Water Vapor Transmission Rate Test The sealing materials of Examples 1-3 and Comparative Examples 1-2 were tested for water vapor transmission rate according to the method in GB / T29755-2013. The results are shown in Table 6.

[0041] Table 6

[0042] In Example 1-3, precipitated silica is modified in two steps, including sodium modification and cross-linked dextran modification, and then used as a reinforcing filler for a sealing material. The sealing material can finally maintain a low water vapor permeability. Comparative Example 1 In the preparation method of cross-linked dextran-modified precipitated silica, the sodium modification step of the precipitated silica is omitted, and the untreated precipitated silica is directly modified with cross-linked dextran. When the amount remains unchanged, it is used as a raw material for the sealing material, which will cause the water vapor permeability of the sealing material to increase to a large extent; In the preparation method of the precipitated silica modified with cross-linked dextran in Comparative Example 2, the cross-linked dextran modification step is omitted, and the sodium-modified precipitated silica obtained in the sodium modification step of the precipitated silica is directly used as the raw material of the sealing material while keeping the dosage unchanged. This will cause the water vapor permeability of the sealing material to increase seriously.

[0043] Test Example 7 Antibacterial and Antifungal Performance Test The sealing materials of Examples 1-3 and Comparative Examples 1-2 were tested for antibacterial and mildew resistance according to the method in GB / T13477.25-2024. The test strains included Penicillium serrata, Penicillium citrinum, Trichoderma viride, and Sphaerotheca brevis. The mildew resistance grade was used as an evaluation index. The results are shown in Table 7.

[0044] Table 7

[0045] In Example 1-3, precipitated silica is modified in two steps, including sodium modification and cross-linked dextran modification, and then used as a reinforcing filler for a sealing material. The sealing material finally has excellent antibacterial and anti-mildew properties and maintains a high level of mildew resistance to different mildews. Comparative Example 1 In the preparation method of cross-linked dextran-modified precipitated silica, the sodium modification step of precipitated silica is omitted, and the untreated precipitated silica is directly modified with cross-linked dextran. When the amount remains unchanged, it is used as a raw material for the sealing material, which will lead to a decrease in the mold resistance level of the sealing material; In the preparation method of precipitated silica modified with cross-linked glucan, the cross-linked glucan modification step is omitted, and the sodium-modified precipitated silica obtained in the sodium modification step of the precipitated silica is directly used as the raw material of the sealing material while keeping the dosage unchanged. This will lead to a decrease in the mildew resistance level of the sealing material, especially the mildew resistance level of Penicillium citrinum and Trichoderma viride, which will decrease more seriously.

Claims

1. A single-component deacetated silicone rubber sealing material that is resistant to stains and mildew, characterized in that: The raw material components of the sealing material are composed of α, ω-dihydroxy polydimethylsiloxane, dimethyl silicone oil, cross-linked dextran modified precipitated silica, a cross-linking agent, and an organic tin catalyst, and the mass ratio of the components is 110-140:30-40:14-16:6-8:4.5-5.5; The preparation method of the cross-linked dextran-modified precipitated silica comprises sodium modification of the precipitated silica and cross-linked dextran modification; The method for sodium modification of precipitated silica comprises washing the precipitated silica with deionized water at 45-55° C. until the conductivity of the deionized water is less than 1.5-2.0 μs / cm, stopping washing, and then drying to constant weight to obtain washed precipitated silica, and then mixing the washed precipitated silica, sodium hydroxide, aluminum hydroxide, sodium silicate, and solvent deionized water, controlling the temperature to 66-70° C., stirring for 280-320 min, and filtering, washing, and drying after stirring to obtain sodium-modified precipitated silica; The mass ratio of the precipitated white carbon black, sodium hydroxide, aluminum hydroxide, sodium silicate, and deionized water for solvent is 85-115:3.5-4.5:11-13:17-23:110-140; The cross-linked dextran modification method comprises: mixing the cross-linked dextran with an acetic acid solution, stirring to completely dissolve the cross-linked dextran solution, and then heating the cross-linked dextran solution to 92-97° C., adding polyvinyl alcohol, and continuing to stir for 15-25 minutes, and then adding sodium-modified precipitated silica and N,N-methylenebisacrylamide, keeping the temperature constant, and continuing to stir for 65-75 minutes. After the stirring is completed, filtering, washing, and drying are performed, and then the temperature is controlled to 405-420° C., and the dried product is subjected to high-temperature treatment for 110-130 minutes. After the treatment is completed, cooling is performed to obtain cross-linked dextran-modified precipitated silica; The mass ratio of the cross-linked dextran to the acetic acid solution is 1:6.5-7.5; The concentration of the acetic acid solution is 4.5-5.5wt%; The mass ratio of the cross-linked dextran solution, polyvinyl alcohol, sodium-modified precipitated silica, and N,N-methylenebisacrylamide is 700-800:75-125:250-350:0.9-1.

1.

2. The one-component deacetated silicone rubber sealing material that is resistant to stains and mildew according to claim 1, characterized in that: In the raw material components of the sealing material, the crosslinking agent is methyltriacetoxysilane, and the organic tin catalyst is dibutyltin diacetate.

3. The one-component deacetated silicone rubber sealing material with antifouling and anti-mildew properties according to claim 1, characterized in that: In the sodium modification step of precipitated silica, the purity of precipitated silica is 95.44 wt%, the particle size is 15 μm, and the specific surface area is 177 m 2 / g.

4. The one-component deacetated silicone rubber sealing material with antifouling and mildew resistance according to claim 1, characterized in that: In the cross-linked dextran modification step, the model of the cross-linked dextran is G15.

5. The one-component deacetated silicone rubber sealing material with antifouling and mildew resistance according to claim 1, characterized in that: The preparation method of the sealing material comprises the following steps: stirring α, ω-dihydroxy polydimethylsiloxane under vacuum for 15-25 minutes, adding a cross-linking agent, continuing stirring for 10-20 minutes, adding cross-linked dextran-modified precipitated silica and dimethyl silicone oil, continuing stirring for 15-25 minutes, and finally adding an organic tin catalyst, stirring for 25-35 minutes, discharging and packaging, and obtaining a single-component deacetated silicone rubber sealing material that is resistant to dirt and mildew.

Citation Information

Patent Citations

  • Preparation method for low-temperature-resistant deacidified room-temperature vulcanized silicone rubber

    CN104194347A

  • Methyl silicone oil-resistant single-component room temperature curing type sealant

    CN106833506A

  • Single-component high-transparency ketoxime-removing type room temperature vulcanized silicone rubber

    CN113980470A

  • Deacetonized single-component matte silicone rubber adhesive and preparation method thereof

    CN116925691A

  • High-adhesive one-component deoximation type room-temperature vulcanized silicone rubber sealant and preparation method therefor

    WO2015158257A1